Analisis Peningkatan Kinerja Integrasi Jaringan Pelayanan Transportasi Pariwisata Dengan Menggunakan Important Performance Analysis (IPA) - ., Dewanti; Nugroho, Deni Prasetio; Harmanto, Jan Prabowo (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2024)
The performance of transportation service integration in tourist areas needs to be improved to attract more tourists. Key factors that contribute to supporting tourism include the availability of supporting sectors such as accommodation services, tourist attractions, travel services, destination management, and transportation. The analysis method used Importance Performance Analysis (IPA), which assessed 16 indicators based on connectivity, ease of use, safety, security, comfort, and amenities. The results of the IPA analysis identified the main priority areas for improvement: the availability of service information centers, public transportation maps, lighting facilities, ease of accessing intermodal information, and ease of ticket reservations. Maintaining performance in areas such as ease of using transportation, availability of hotel services, current travel time, and social environment ambiance is also important. Conversely, areas such as shading for pedestrian paths, parking space availability, and pedestrian comfort were found to have poor performance and low importance. On the other hand, areas such as conflicts among pedestrians, conflicts between pedestrians and other modes of transportation, availability of restaurants/shops, and service schedule suitability were found to have good performance but tended to be excessive. These findings provide valuable insights for improving the integration of transportation services in tourist areas. ABSTRAK Kinerja integrasi pelayanan transportasi kawasan wisata perlu ditingkatkan untuk menarik wisatawan. Ketersediaan sektor penunjang pariwisata seperti jasa penginapan, daya tarik wisata, sektor penyelenggaraan perjalanan, pengelolaan tempat tujuan wisata dan transportasi menjadi kunci layanan untuk mendukung pariwisata. Metode analisis yang digunakan adalah Importance Performace Analysis (IPA). Penilaian IPA ini dilakukan pada 16 indikator berdasarkan dari 6 kriteria yaitu konektivitas, kemudahan, keselamatan, keamanan, kenyamanan dan amenitas. Berdasarkan hasil analisis IPA yang dilakukan maka didapatkan hasil prioritas utama dan harus diperbaiki kinerjanya karena sangat penting: ketersediaan pusat informasi layanan, ketersediaan peta transportasi publik, fasilitas penerangan, kemudahan akses informasi alih moda, kemudahan reservasi tiket. Mempertahankan kinerja: kemudahan menggunakan transportasi, ketersediaan jasa hotel, waktu tempuh saat ini, suasana lingkungan sosial. Kinerja tidak baik dan tidak penting: peneduh jalur pejalan kaki, luas parkir, kenyamanan jalan kaki. Kinerja baik, cenderung berlebihan: konflik sesama pejalan kaki, konflik pejalan kaki dengan moda lain, ketersediaan rumah makan/toko, kesesuaian jadwal layanan.